F. J. Billeskov Jansen, Egill Snorrason og Chr. Lauritz-Jensen (red.): Hans Christian Ørsted. (IFV-energi i/s (Isefjordsværket), 1987. I kommission hos Nyt Nordisk Forlag Arnold Busck). 200 s. - Balle, Søren (Historie/Jyske Samlinger, 1989)
-